Embodied cognition and Christian theological conceptions of the human person - Wallace, R (2023)

(untitled)
This thesis examines a paradigm within the cognitive sciences now generally known as “embodied cognition” (EC) and its implications for theological anthropology, specifically Christian doctrines of the soul/mind. The importance of “embodiment” has gained increasing traction in theology. But while scientific evidence of embodiment has been recognized as a tool for understanding doctrines within theology, as well as theological inquiry itself, as yet there has been little engagement with the metaphysical background to this integration. I argue that embodied cognition offers the most comprehensive scientific and philosophical paradigm from which to understand embodiment, but significantly it has seen very little rigorous engagement by theologians. Some of the most recent engagement (Watts 2021) lacks philosophical rigor and theological depth. I identify three areas of potential improvement around which the thesis is organized: methodological, philosophical, and theological. Methodologically, EC cannot be treated as a unified approach, however, I take an abductive tack. In adopting the logic of embodied cognition, I turn my gaze to questions of the mind/soul to see if a new way of thinking about human beings comes to light. I then show that current discussions surrounding the soul/body are trapped between physicalism or Cartesian substance dualism. Embodied cognition has come to be associated with physicalism, making it difficult for many Christians to accept because of physicalism’s eschatological implications. Cartesian substance dualism is equally problematic from an empirical perspective. However, this obscures a third option, Thomistic hylomorphism, which shows strong resonances with embodied cognition. Both hylomorphism and EC are biological approaches to the soul that emphasize holism, dynamism, and organization. In addition, hylomorphism relieves many of the theological challenges of physicalism because it allows for the continuance of the soul after death. Scientifically and theologically viable, embodied cognition as a modern take on hylomorphism coheres with Christian eschatological requirements.